2014
DOI: 10.1109/tcomm.2014.2364188
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transceiver Power Consumption on the Energy Efficiency of Zero-Forcing Detector in Massive MIMO Systems

Abstract: Abstract-We consider the impact of transceiver power consumption on the energy efficiency (EE) of the Zero Forcing (ZF) detector in the uplink of massive MIMO systems, where a base station (BS) with M antennas communicates coherently with K single antenna user terminals (UTs). We consider the problem of maximizing the EE with respect to (M, K) for a fixed sum spectral efficiency. Through analysis we study the impact of system parameters on the optimal EE. System parameters consists of the average channel gain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 19 publications
1
78
0
Order By: Relevance
“…The research results illustrated that the maximal EE is achieved at some finite number of transceiver antennas when there is a non-zero circuit power per antenna. Similarly, the studies in [41] also demonstrated that it is optimal from the perspective of EE to have a few transceiver antennas when the transceiver design is power inefficient.…”
Section: Introductionmentioning
confidence: 90%
“…The research results illustrated that the maximal EE is achieved at some finite number of transceiver antennas when there is a non-zero circuit power per antenna. Similarly, the studies in [41] also demonstrated that it is optimal from the perspective of EE to have a few transceiver antennas when the transceiver design is power inefficient.…”
Section: Introductionmentioning
confidence: 90%
“…Equation (14) is used to calculate the remaining renewable energy. The available value of renewable energy for period can be calculated by (15), which fully utilizes (8) and (9). Equations (16) and (17) denote the transmitting power constraint for period and the QoS constraint for MT .…”
Section: Problem Formulationmentioning
confidence: 99%
“…Considering the transmit power and the circuit power in massive MIMO systems, a power consumption model has been proposed to help optimize the energy efficiency of multi-cell mobile communication systems by selecting the optimal number of active antennas [23]. When the sum spectrum efficiency was fixed, the impact of transceiver power consumption on the energy efficiency of ZF detector was investigated for the uplinks of massive MIMO systems [24]. Considering the power cost by RF generation, baseband computing, and the circuits associated with each antenna, simulation results in [25] illustrated that massive MIMO macro cells outperforms LTE macro cells in both spectrum and energy efficiency.…”
Section: Introductionmentioning
confidence: 99%